EFEKTIFITAS PENGGUNAAN SISTEM INFORMASI TERINTEGRASI (SIMASTER) DALAM PEMBELAJARAN JARAK JAUH (Studi Kasus Pembelajaran Jarak Jauh Di Fakultas Tarbiyah IDIA Prenduan) - Ardiyanti; Afifah Tidjani (Jurnal Ilmiah AL-Jauhari: Jurnal Studi Islam dan Interdisipliner, 2021)
The Covid-19 pandemic situation has imposed a change in the design of the learning process that is normally face-to-face, as in general, to online learning. In this condition, students are required to do more effort in understanding the subject through online discussions. Online learning is also implemented in IDIA Prenduan by using the Integrated Information System (SIMASTER). The purpose of this study is to determine the extent to which the SIMASTER is effective in the online learning process, specifically in the Tarbiyah faculty. This research uses a qualitative field approach. And the data collection through interviews, documentation, and observation. And for data analysis, using reduction, presentation, and verification. The result showed that the use of Integrated Information System (SIMASTER) in online learning was effective because it learning it was continuous even in a pandemic. Although it needs improvement because the system is new and needs development to be effective. Although is used still needs support for other applications.